Taxonomic studies on the genus Delphinium (Ranunculaceae) from China (XVII): Five new synonyms of D. afghanicum, a newly recorded species for China - Li, Hui-Min; Yuan, Qiong; Yang, Qin-Er (Phytotaxa, 2019)
Delphinium aktoense, D. kaschgaricum, D. kunlunshanicum, D. wuqiaense and D. zhangii (Ranunculaceae) were all described from the region of eastern Pamir-western Kunlun Shan in western Xinjiang, China. Critical observations on both herbarium specimens (including type material) and living plants demonstrate that they are indistinguishable from each other and are all conspecific with D. afghanicum, a species previously known only from Afghanistan.